Heart Failure-Inducible Gene Therapy Targeting Protein Phosphatase 1 Prevents Progressive Left Ventricular Remodeling - Miyazaki, Yosuke; Ikeda, Yasuhiro; Shiraishi, Kozo; Fujimoto, Shizuka N.; Aoyama, Hidekazu; Yoshimura, Koichi; Inui, Makoto; Hoshijima, Masahiko; Kasahara, Hideko; Aoki, Hiroki; Matsuzaki, Masunori (PLOS ONE, 2012)
Background The targeting of Ca2+ cycling has emerged as a potential therapy for the treatment of severe heart failure. These approaches include gene therapy directed at overexpressing sarcoplasmic reticulum (SR) Ca2+ ATPase, or ablation of phospholamban (PLN) and associated protein phosphatase 1 (PP1) protein complexes. We previously reported that PP1β, one of the PP1 catalytic subunits, predominantly suppresses Ca2+ uptake in the SR among the three PP1 isoforms, thereby contributing to Ca2+ downregulation in failing hearts. In the present study, we investigated whether heart-failure-inducible PP1β-inhibition by adeno-associated viral-9 (AAV9) vector mediated gene therapy is beneficial for preventing disease progression in genetic cardiomyopathic mice. Methods We created an adeno-associated virus 9 (AAV9) vector encoding PP1β short-hairpin RNA (shRNA) or negative control (NC) shRNA. A heart failure inducible gene expression system was employed using the B-type natriuretic protein (BNP) promoter conjugated to emerald-green fluorescence protein (EmGFP) and the shRNA sequence. AAV9 vectors (AAV9-BNP-EmGFP-PP1βshRNA and AAV9-BNP-EmGFP-NCshRNA) were injected into the tail vein (2×1011 GC/mouse) of muscle LIM protein deficient mice (MLPKO), followed by serial analysis of echocardiography, hemodynamic measurement, biochemical and histological analysis at 3 months. Results In the MLPKO mice, BNP promoter activity was shown to be increased by detecting both EmGFP expression and the induced reduction of PP1β by 25% in the myocardium. Inducible PP1βshRNA delivery preferentially ameliorated left ventricular diastolic function and mitigated adverse ventricular remodeling. PLN phosphorylation was significantly augmented in the AAV9-BNP-EmGFP-PP1βshRNA injected hearts compared with the AAV9-BNP-EmGFP-NCshRNA group. Furthermore, BNP production was reduced, and cardiac interstitial fibrosis was abrogated at 3 months. Conclusion Heart failure-inducible molecular targeting of PP1β has potential as a novel therapeutic strategy for heart failure.